A Review of the Selective Laser Melting Lattice Structures and Their Numerical Models. Issue 12 (3rd September 2020) - Alomar, Zaki; Concli, Franco
Abstract : The high‐fidelity metal additive manufacturing (MAM) processes promote the development of complex lattice structure designs with tailored physical and mechanical properties. Particularly, the unique characteristics of the selective laser melting (SLM) lattice structures make them desirable in many leading application areas. However, the full‐scale adoption of lattices is limited by the lack of a standard numerical model that can reliably predict and assess their mechanical and failure response. Most of the studies follow a unique methodology that differs greatly from their counterparts. In this context, herein a review of the numerical methods developed specifically to analyze the mechanical behavior of lattice structures is presented, while the potentials and limitations of each model are showcased. The numerical models' key differences are identified, and their impacts on the finite models are highlighted. Correlations between the relative density and the compressive mechanical properties of the collected data are established following the Gibson–Ashby model. In addition, an overview of the lattice's designs, properties, performance, and defects is provided. Overall, this review is intended to provide the reader with comprehensive knowledge about lattice structures and accelerate the process of developing a reliable yet computationally inexpensive standardized numerical model. Abstract : Herein an introduction to as well as an overview of lattice designs and structures is provided. Correlations are established based on the Gibson–Ashby model. Defects induced by the selective laser melting (SLM) process are highlighted, and SLM lattice structures' performance is focused on. The numerical models are addressed, and a summary of the conclusions is presented.